2010
DOI: 10.1111/j.1365-2141.2010.08147.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of severe malarial anaemia in a holoendemic Plasmodium falciparum transmission area

Abstract: SUMMARYSevere malarial anaemia (SMA) is a common complication of Plasmodium falciparum infections, resulting in mortality rates that may exceed 30% in paediatric populations residing in holoendemic transmission areas. One strategy for reducing the morbidity and mortality associated with SMA is to identify clinical predictors that can be readily recognized by caregivers for prompt therapeutic interventions. To determine clinical predictors of SMA, Kenyan children (3-36 mos., n=671) presenting with acute illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 55 publications
8
32
0
Order By: Relevance
“…Features such as tachypnoea, tachycardia, hepatomegaly, gallop rhythm, lethargy and grunting, which are characteristic of heart failure in anaemic children, are thought to arise from lactic acidosis. 4,13 Consistent with previous studies, 12,13 high-density parasitaemia was neither significantly related nor a predictor of death from severe anaemia. A study on the clinical predictors of severe malaria anaemia in a holo-endemic P. falciparum transmission area found that children with uncomplicated malaria had more peripheral parasitaemia, geomean parasitaemia and proportion of high-density parasitaemia than those with severe anaemia.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Features such as tachypnoea, tachycardia, hepatomegaly, gallop rhythm, lethargy and grunting, which are characteristic of heart failure in anaemic children, are thought to arise from lactic acidosis. 4,13 Consistent with previous studies, 12,13 high-density parasitaemia was neither significantly related nor a predictor of death from severe anaemia. A study on the clinical predictors of severe malaria anaemia in a holo-endemic P. falciparum transmission area found that children with uncomplicated malaria had more peripheral parasitaemia, geomean parasitaemia and proportion of high-density parasitaemia than those with severe anaemia.…”
Section: Discussionsupporting
confidence: 79%
“…A study on the clinical predictors of severe malaria anaemia in a holo-endemic P. falciparum transmission area found that children with uncomplicated malaria had more peripheral parasitaemia, geomean parasitaemia and proportion of high-density parasitaemia than those with severe anaemia. 13 Our findings therefore support the hypothesis that immune response to P. falciparum rather than the cumulative parasite burden may be the primary factor responsible for the development and promotion of severe malaria anaemia in holo-endemic regions. 13 Of our patients, 26% had bacteraemia and 55.2% of those who died had bacteraemia.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore to test this hypothesis, we characterized the ex vivo ability of peripheral lymphocytes and CD4+ T-cell sub-populations to produce IFN-γ and IL-17 in acutely infected children presenting with non-SMA and SMA. In agreement with previous reports, children presenting with SMA had leukocytosis [56, 57]. In addition, our observation of elevated levels of lymphocytes expressing IFN-γ in children with SMA and memory-like CD4+ T-cells expressing IL-17 in children with non-SMA, suggests in vivo induction of these cells as has been reported in animal models [43, 5860].…”
Section: Discussionsupporting
confidence: 93%